Understanding Relations Between Scripts II : Early Alphabets - Philippa M. Steele; Philip J. Boyes (Oxbow Books, 2020)
Contexts of and Relations between Early Writing Systems (CREWS) is a project funded by the European Research Council under the European Union's Horizon 2020 research and innovation programme (grant agreement No. 677758), and based in the Faculty of Classics, University of Cambridge. Understanding Relations Between Scripts II: Early Alphabets is the first volume in this series, bringing together ten experts on ancient writing, languages and archaeology to present a set of diverse studies on the early development of alphabetic writing systems and their spread across the Levant and Mediterranean during the second and first millennia BC. By taking an interdisciplinary perspective, it sheds new light on alphabetic writing not just as a tool for recording language but also as an element of culture.